The geolect of Pasvalys: a dialectometric approach to dialectal features - Čepaitienė, Agnė (Taikomoji kalbotyra, 2019)
Using dialectometric methods and instruments, the article analyzes one of the new dialectal derivatives – the geolect of Pasvalys, located in the northern part of Eastern Aukštaitians of Panevėžys. The aim is to find the strong and weak dialectal features of this geolect and to identify its dominant dialectal variants.10-hour recordings and 60 simple-structure sentences reflecting the primary, secondary and tertiary dialectal features have been analyzed in order to achieve the research aim. The recorded sentences were uttered by nine respondents of three generations: the oldest, the middle-aged and the youngest. The respondents live in the regions of Joniškėlis, Pasvalys and Daujėnai, which are interconnected by the strongest, closest, densest and the most complex socio-cultural networks.The dialectal data, which includes the recorded sentences transcribed by IPA, was statistically calculated and quantified using the tools of the Gabmap software. The network pseudo map, reference point pseudo maps, cluster analysis pseudo maps and differential dialectal features were analyzed. The quantitative data analysis has shown that the dialectal variant used in the regions of Joniškėlis, Pasvalys and possibly Daujėnai is affected by the processes of convergence. The most stable dialectal features are used in the region of Joniškėlis. They (as well as the forms of standard language) change or supplement the dialectal features of the subdialects of Pasvalys and Daujėnai spoken in the eastern part of the area of Eastern Aukštaitians of ​​Panevėžys (the direction of its spread is the eastern part of the area of ​​the subdialect) and form the basis of the dialectal features of Pasvalys geolect.Both stable and changing primary, secondary and tertiary dialectal features were found in the speech of the respondents of all the three-generations. The change of dialectal features, or convergence, is the strongest in the youngest generation. It is similarly strong in the middle-aged and in the oldest generations. However, in the speech of young people, most of the primary dialectal features coexist with the secondary and tertiary ones.Thus, the formation of Pasvalys geolect is based on the more stable (rather than changing) strong variant used in Joniškėlis, which is marked by a high degree of vitality.
Keywords: Pasvalys geolect; Eastern Aukštaitians of Panevėžys; dialect change; IPA; dialectometry